STRATEGIES FOR DIGITIZATION AND VISUALIZATION OF BUSINESS IDENTITY IN EMPOWERING MSMEs IN TAMBAK WEDI VILLAGE - Oktavia Eka Ardyanti; Satria Tegar Sanubari; Carrisa Irma Dehlia; Ahmad Asyroful Ibad; Andi Muchammad Fadel Abista; A. Muammar Alawi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service aims to contribute to the Tambak Wedi Village community in the Micro, Small and Medium Enterprises (MSME) sector to empower their businesses. The method used for this research is PAR (Participatory Action Research) with 5 stages starting from problem identification to evaluation. The targets of the activity included 10 MSMEs out of a total of 50 MSMEs recorded in Tambak Wedi Village. The results of this activity increase the understanding of MSME actors regarding the digitization of business locations through Google Maps tagging, visual business identity such as logos and banners, and the use of digital platforms in conducting promotions to increase sales and business branding.